Novelties in the pharmacological approaches for chronic heart failure: new drugs and cardiovascular targets - Correale, Michele; Tricarico, Lucia; Croella, Francesca; Alfieri, Simona; Fioretti, Francesco; Brunetti, Natale Daniele; Inciardi, Riccardo M.; Nodari, Savina (Frontiers in Cardiovascular Medicine, 2023)
Despite recent advances in chronic heart failure management, the prognosis of heart failure (HF) patients remains poor. This emphasizes the need for developing new drugs targeting novel pathways, beyond neurohumoral and hemodynamic modulation approach, such as cardiomyocyte metabolism and myocardial interstitium. This review summarizes main evidence on new possible pharmacological targets for the treatment of HF patients, mainly focusing on drugs acting on cardiac metabolism, GCs-cGMP pathway, mitochondrial function and intracellular calcium dysregulation.